Electrodeposited Ru Nanoparticles for Electrochemical Reduction of NAD(+) to NADH - Rahman, Gul; Lim, Ji Yeon; Jung, Kwang-Deog; Joo, Oh-Shim (ESG, 2011)
Ruthenium nanoparticles (RuNP) were deposited on glassy carbon (GC) substrate by cathodic electrodeposition method. The electrocatalytic properties of RuNP deposits were characterized by scanning electron microscopy, cyclic voltammetry and linear sweep voltammety. Rusults of these studies showed that very small sized RuNP are deposited with significantly large particle density which is attributed to the controlled deposition potential. The resulted RuNP/GC electrodes showed remarkable catalytic activity for electrochemical reduction of NAD(+) to NADH, indicating its potential for electrocatalytic applications.
Keywords: RUTHENIUM NANOPARTICLES